The Role of Project Management Information Systems Towards the Project Performance The Case of Construction Projects in United Arab Emirates - Obeidat, Mohammad Abdul Qadir; Aldulaimi, Saeed Hameed (International Review of Management and Marketing, 2016)
Project Management Information Systems (PMIS) has become an essential tool in contemporary organizations. 21st century project managers cannot afford the losses, delays, and disappointments often triggered by redundant projects. PMIS is even more critical for business organizations, where profitability and long-term sustainability is pegged on competitively performing projects. PMIS has thus become a strategic resource for project managers when seeking optimal level of project performance. United Arabs Emirates has gradually transformed to an epicentre of economic development in the Middle East. In pursuit of economic development and globalization, UAE has made unprecedented investments in the construction of infrastructural and networking systems. The present study established that construction represents perhaps the most advanced and progressive market-based industries in UAE. Construction projects are now defined by a complex matrix of profitability, performance, and cost-time balance. After collecting questionnaire data from a purposive sample of 20 project managers in UAE, the survey established a positive correlation (r = + 0 .72) between the use of PMIS and project performance. The findings validated the hypothesis of the study, and affirmed that, there is a significant positive relationship between the quality, information output and user influence of PMIS and project performance when implementing construction projects in UAE. Future research should cover a more reliable sample size and triangulate the data collection instruments to generate more reliable findings. Further, future research should focus on establishing how PMIS improve project management while in actual practice, rather than exclusively relying on the admissions of relatively biased project managers whose core interest is display their companies as market leaders in practice. Keywords: Project Management Information Systems, PMIS, Project Management, Construction Projects, UAE, Project Outcomes, Project Objectives JEL Classification: O22